2009
DOI: 10.1038/sj.bjc.6604985
|View full text |Cite
|
Sign up to set email alerts
|

The BAG-1 cochaperone is a negative regulator of p73-dependent transcription

Abstract: High-level expression of Bcl-2 associated athanogene (BAG-1) protects cancer cells from stress-induced cell death and growth inhibition. These protective effects of BAG-1 are dependent on interactions with the HSC70 and HSP70 chaperones. However, the key stress-response molecules that are regulated by a BAG-1/chaperone mechanism have not been identified. In this study, we investigated the effects of BAG-1 overexpression on the function of p53 family proteins, p53, p63 and p73. Overexpression of BAG-1 isoforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Importantly, the nuclear isoform of BAG-1 (BAG-1L) has been implicated in the control of transcription (reviewed in [ 16 ]). This may occur through direct interaction of BAG-1 with DNA [ 17 , 18 ], or through interaction with DNA-binding proteins such as nuclear hormone receptors [ 19 , 20 ], the retinoblastoma protein [ 13 ] or p73 [ 21 ]. More recently we have shown that, through direct interaction with homodimeric p50 NF-κB complexes, BAG-1 can regulate NF-κB dependent transcription at a sub-set of NF-κB target genes including the epidermal growth factor receptor ( EGFR ) and COX-2 ( PTGS2 ) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the nuclear isoform of BAG-1 (BAG-1L) has been implicated in the control of transcription (reviewed in [ 16 ]). This may occur through direct interaction of BAG-1 with DNA [ 17 , 18 ], or through interaction with DNA-binding proteins such as nuclear hormone receptors [ 19 , 20 ], the retinoblastoma protein [ 13 ] or p73 [ 21 ]. More recently we have shown that, through direct interaction with homodimeric p50 NF-κB complexes, BAG-1 can regulate NF-κB dependent transcription at a sub-set of NF-κB target genes including the epidermal growth factor receptor ( EGFR ) and COX-2 ( PTGS2 ) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this may well be a cell type-and stimulus-specific effect, as RAF-1 is known to elicit prosurvival signals through ERK-mediated phosphorylation of pro-and anti-apoptotic effectors such as BAD, BIM and BCL-2 (Kolch, 2000). Recently, Wang et al demonstrated BAG-1's ability to interact with and inhibit the transactivating function of p73, suggesting that this may contribute to BAG-1-mediated survival given p73's known role as a regulator of stress-induced apoptosis (Wang et al, 2009). Thus, BAG-1's prosurvival effects are likely to be mediated through multiple pathways depending on the cellular context and reflecting its numerous and varied binding partners.…”
Section: Introductionmentioning
confidence: 99%
“…Although it was initially identified as a Bcl-2 binding protein to suppress apoptosis [7], Bag-1 has been known to interact with and regulate the activity of other proteins. For example, Bag-1 interacts with and inhibits the function of the tumor suppressor p73 [8]. Furthermore, the medium isoform, Bag-1M is increased in the hippocampus of Alzheimer's disease patients and binds to Tau protein and amyloid precursor protein (APP), and overexpressed Bag-1M induces increased level of Tau and APP that are related with the pathology and treatment of Alzheimer disease [9,10].…”
Section: Introductionmentioning
confidence: 99%